Batas Tanggung Jawab Notaris terhadap Kebenaran Materiil dalam Akta Otentik Berdasarkan Keterangan Para Pihak - Devina Pinkan Febriana; Aminah Aminah (Journal of Creative Student Research, 2026)
This study examines the boundary of notary responsibility regarding material truth in authentic deeds based on statements made by the parties. The research focuses on the normative legal framework governing notarial authority and the extent to which a notary can be held responsible for the accuracy of substantive information contained in deeds. Using a normative legal research method, this study analyzes statutory regulations, doctrinal concepts, and relevant court decisions to identify inconsistencies between legal norms and judicial practice. The findings indicate that notaries are principally responsible for formal truth, including procedural and administrative validity of deeds, while material truth remains the responsibility of the parties who provide the statements. However, judicial practice shows varying interpretations, particularly when deeds are disputed due to false or inaccurate information provided by the parties. Such conditions create legal uncertainty regarding the limits of notarial liability. This study concludes that notarial responsibility should remain confined to formal aspects unless there is proven involvement, negligence, or intentional misconduct by the notary. Clear normative boundaries are required to ensure legal certainty and maintain the functional distinction between notarial duties and party accountability in the creation of authentic deeds.